2007
DOI: 10.1103/physreve.76.021507
|View full text |Cite
|
Sign up to set email alerts
|

Crossover of aging dynamics in polymer glass: From cumulative aging to noncumulative aging

Abstract: The aging behavior of polymer glass, poly(methyl methacrylate), has been investigated through the measurement of ac dielectric susceptibility at a fixed frequency after a temperature shift ∆T (≤ 20 K) between two temperatures, T1 and T2. A crossover from cumulative aging to non-cumulative aging could be observed with increasing ∆T using a twin temperature (T -) shift measurement. Based on a growth law of a dynamical coherent length given by activated dynamics, we obtained a unique coherent length for positive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The memory effect during aging is another interesting phenomenon that is shown by thin films, as first observed by Kovacs. 22 Later, Fukao et al 23,24 and Bellon et al 21 confirmed this effect in PMMA thin films via dielectric studies. They adopted a temperature cycle mode in which the sample was first cooled to a temperature, T 1 , which was <T g , and kept at T 1 for a period, τ 1 .…”
Section: T H Imentioning
confidence: 99%
See 1 more Smart Citation
“…The memory effect during aging is another interesting phenomenon that is shown by thin films, as first observed by Kovacs. 22 Later, Fukao et al 23,24 and Bellon et al 21 confirmed this effect in PMMA thin films via dielectric studies. They adopted a temperature cycle mode in which the sample was first cooled to a temperature, T 1 , which was <T g , and kept at T 1 for a period, τ 1 .…”
Section: T H Imentioning
confidence: 99%
“…Advancing literature on the confinement effect in polymer systems has confirmed some unusual behaviors, such as (i) the strong dependence of the glass transition temperature, T g , on the thickness and interface conditions; (ii) the acceleration and deacceleration of the aging dynamics in thin and ultrathin films, respectively; (iii) the negative thermal expansion (NTE) of some glassy polymers even after prolonged, multiple annealing; and (iv) the memory and rejuvenation effects on the aging dynamics. …”
Section: Introductionmentioning
confidence: 99%